The multiplicity of knowledge and the trembling of institutions - Vololona Rabeharisoa (Revue d'anthropologie des connaissances)
In the last few years, the engagement of patient organizations –and more broadly groups concerned with an issue involving scientific knowledge– in the production of knowledge has become a classic topic in social sciences. The experiential knowledge produced by these groups and organizations is a challenge for scientific institutions. This article proposes a few paths that researchers interested in the anthropology of knowledge could explore in order to understand how scientific institutions become (or not) sensitive to such experiential knowledge and to the transformations that this knowledge could induce in the governance of research and innovation.